2009
DOI: 10.9775/kvfd.2010.1672
|View full text |Cite
|
Sign up to set email alerts
|

Canlı Maya Kültürünün (Saccharomyces cerevisiae) Toklularda Rumen Fermentasyonu ve Besin Madde Yıkılabilirliği Üzerine Etkileri

Abstract: SummaryThis study was carried out in two experiments. Experiment 1 was conducted with six ruminally-cannulated one-year old Kangal Akkaraman male lambs, using a crossover design with 2 periods to determine the effects of live yeast culture supplementation on rumen fermentation. Yearlings were either supplemented with 4 g/d of Saccharomyces cerevisiae (BeneSacc, 4x10 9 CFU/g) or not supplemented (control). Animals were penned individually, and were fed a diet composed of 25% forage and 75% concentrate for six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
1
0
3
Order By: Relevance
“…Bulguların yapılan diğer çalışmalarla (28,41,42) uyum içerisinde olduğu görülmüştür. Amonyak azotundaki bu yükselmenin nedeni mikroorganizmalar tarafından proteolizin ve proteinlerin deaminasyonunun artması olabileceği belirtilmiştir (20).…”
Section: Tartışma Ve Sonuçunclassified
See 2 more Smart Citations
“…Bulguların yapılan diğer çalışmalarla (28,41,42) uyum içerisinde olduğu görülmüştür. Amonyak azotundaki bu yükselmenin nedeni mikroorganizmalar tarafından proteolizin ve proteinlerin deaminasyonunun artması olabileceği belirtilmiştir (20).…”
Section: Tartışma Ve Sonuçunclassified
“…Canlı maya kültürü ilavesinin rumende asetik asit ve bütirik asit miktarlarını artırdığı, propiyonik asit miktarını azalttığı saptanmıştır (18,29,32). Bazı çalışmalarda ise asetik asit ve bütirik asit miktarlarının azaldığı, propiyonik asit miktarının ise arttığı bildirilmiştir (27,28). Rasyonlara canlı maya kültürü ilavesi ile selülolitik bakteri sayısının artabileceği ve bu bakterilerin yapılarındaki azotlu bileşenleri sentezlemek için amonyağı kullanmaları ile rumende amonyak seviyesinin düşebileceği ifade edilmiştir (12).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…These differences may depend on many factors such as diet composition, forage to concentrate ratio, type of forage feed, yeast dose, feeding strategy and stage of lactation [1] . Saccharomyces cerevisiae vary widely in efficiency, primarily because of differences in strain, the viability of yeast cells, and theirs dosage [2] . Studies reported that yeast supplementation increased growth, feed intake and nutrient utilization in Black Bengal kids [3] , improved feed conversion ratio of Awassi lambs [4] .…”
Section: Introductionmentioning
confidence: 99%